Association of Vitamin D Receptor Gene Polymorphism (Taq1) in Sudanese Children with Type 1 Diabetes Mellitus at Gezira State, Sudan. - A Hamza, Mohammed; E. Khalid, Khalid; K Saeed, Osman; M Haroun, Huda (مجلة الجزيرة للعلوم الصحية; مجلد 14 عدد 2 (2018), 2018)
Introduction: Diabetes mellitus describes a metabolic disorder of multiple aetiology characterized by chronic hyperglycemia with disturbances of carbohydrate, fat and protein metabolism resulting from defects in insulin secretion, insulin action, or both. Objectives: This study aimed to determine the frequency of selected VDR gene polymorphismTaq1(rs731236) single nucleotide polymorphism in diabetic and non-diabetic children to assess its contribution to the susceptibility to type 1 diabetes (T1D). Methods: One hundred children with T1D were enrolled in this study; 50 healthy non-diabetic children served as a control group for detection of VDR gene polymorphism Taq1. This polymorphism was detected by using the polymerase chain reaction (PCR) and restriction fragment polymorphism (RFLP) analysis. Results: There was a significant difference between frequencies of Taq1 (t allele) ((P= 0.05; Odd Ratio = 0.412; 95% CI 0.182 - 0.932). Conclusion: VDR TaqI polymorphism was associated with T1D in Sudanese children. يوصف مرض السكري بأنه من المسببات المرضية المتعددة التي تتميز بفرط  سكر الدم المزمن واضطراب في التمثيل الغذائي ( اضطرابات من الكربوهيدرات والدهون واستقلاب البروتين) الناتج عن نقص في إفراز الأنسولين، عمل الانسولين أو كليهما . هدفت هذه الدراسة لتحديد تكرارات تعدد شكل الجين المستقبل لفايتمين د في مجموعتي المرضي والأصحاء ولتقييم دوره في الإصابة بالسكري عند الأطفال. اشتملت هذه الدراسة علي 100طفل مصابين مرض السكري و50 أصحاء من نفس العمر.تضمنت هذه الدراسة تكرارات تعدد شكل الجين المستقبل لفايتمين د(Taq1)  في مجموعتي المرضي والأصحاء . أظهرت هذه الدراسة ان تكرار الاليل (t) في الجين المسقبل لفايتمين د  يختلف اختلاف ذو معني  عند مجموعة الأصحاء مقارنة  بالمرضي مما يعني ان لهما دور في الحماية من الاصابة بالسكري عند الأطفال . خلصت هذه الدراسة الي ان التعدد في الشكل الجيني لمسقبل فايتمين د (Taq1) لهما علاقة بالإصابة بالسكري النوع الأول عند الاطفال السودانيين.